Sedoanalgesia with midazolam and fentanyl citrate controls probe pain during prostate biopsy by transrectal ultrasound - Tsuji, Fábio Hissachi [UNESP]; Chambó, Renato Caretta [UNESP]; Agostinho, Aparecido Donizeti [UNESP]; Trindade Filho, José Carlos Souza [UNESP]; de Jesus, Carlos Márcio Nóbrega [UNESP] (XMLink, 2014)
To assess the pain intensity of patients administered midazolam and fentanyl citrate before undergoing transrectal ultrasound-guided prostate biopsy. This was a study in patients with different indications for prostate biopsy in whom 5 mg of midazolam and 50 µg of fentanyl citrate was administered intravenously 3 minutes before the procedure. After biopsy, pain was assessed by use of a visual analogue scale (VAS) in three stages: VAS 1, during probe introduction; VAS 2, during needle penetration into prostate tissue; and VAS 3, in the weeks following the exam. Pain intensity at these different times was tested with stratification by age, race, education, prostate volume, rebiopsy, and anxiety before biopsy. Pain was ranked according to the following scores: 0 (no pain), 1-3 (mild pain), 4-7 (moderate pain), and 8-10 (severe pain). Statistical analysis was performed by using Kruskal-Wallis and Wilcoxon two-tailed tests with a significance of 5%. Pain intensity was not influenced by any risk factors. The mean VAS 1 score was 1.95±1.98, the mean VAS 2 score was 2.73±2.55, and the mean VAS 3 score was 0.3±0.9, showing greater pain at the time of needle penetration than in other situations (VAS 2>VAS 1>VAS 3, p=0.0013, p=0.0001, respectively). Seventy-five percent of patients reported a VAS pain scale of less than 3.1 or mild pain. Intravenous sedation and analgesia with midazolam and fentanyl citrate is a good method for reducing pain caused by prostate biopsy, even during probe insertion.
Keywords: Anesthesia and analgesia; Needle biopsy; Pain measurement; Prostate